1994
DOI: 10.1038/ki.1994.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pyruvate on oxidant injury to isolated and cellular DNA

Abstract: Drawing upon the capacity of pyruvate to detoxify H2O2, we demonstrate that pyruvate (i) protects against H2O2-dependent, hydroxyl radical-mediated degradation of isolated DNA; (ii) reduces the amount of 8-hydroxy-2-deoxyguanosine detected following oxidative injury to isolated DNA and (iii) diminishes the amounts of detectable hydroxyl radical generated by a H2O2-dependent system. Compared to mannitol, pyruvate protects weakly against oxidative degradation of DNA induced by a H2O2-independent, hydroxyl radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…To examine further the contribution of alterations in cellular redox to the complications of sickle cell disease, we decreased renal thiol content by administering BSO, an inhibitor of the synthesis of glutathione 26 ; glutathione represents the dominant thiol in tissues. Using this manipulation, we demonstrate marked effects in sickle but not control mice: the kidney in the sickle mouse, exposed to the glutathione-depleting agent, BSO, exhibited extension of vascular congestion from the inner medulla (where RBC congestion is normally exhibited in this unstressed transgenic sickle kidney) into the outer medulla, cortical capillaries, and glomerular capillaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine further the contribution of alterations in cellular redox to the complications of sickle cell disease, we decreased renal thiol content by administering BSO, an inhibitor of the synthesis of glutathione 26 ; glutathione represents the dominant thiol in tissues. Using this manipulation, we demonstrate marked effects in sickle but not control mice: the kidney in the sickle mouse, exposed to the glutathione-depleting agent, BSO, exhibited extension of vascular congestion from the inner medulla (where RBC congestion is normally exhibited in this unstressed transgenic sickle kidney) into the outer medulla, cortical capillaries, and glomerular capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Thiol content was determined by the method based on the reduction of the Ellman reagent, 5,5Ј-dithiobis (2-nitrobenzoic acid), as previously described. 26 …”
Section: The Effect Of Acute Reduction In Renal Thiol Content In Contmentioning
confidence: 99%
“…Seminal studies by Nath and colleagues pointed out that, as an α-ketoacid, pyruvate is capable of scavenging hydrogen peroxide by undergoing decarboxylation and yielding CO 2 and water [2,3]. The relevance of this pathway is that oxidative stress is a key determinant of most forms of acute as well as chronic kidney injury [4].…”
Section: Pyruvate As a Cytoprotective Moleculementioning
confidence: 99%
“…For example, studies by Salahudeen et al 1 and Nath et al 2 showed that pyruvate is a potent H 2 O 2 scavenger, which was assessed in an in vitro system. Furthermore, Salahudeen et al 1 and Nath et al 2 reported that pyruvate administration decreased renal injury after intrarenal H 2 O 2 injection and during the course of the glycerol model of rhabdomyolysisinduced ARF.…”
mentioning
confidence: 99%